Positional Advantages, Consumer Preferences for Indonesian National Rice SPHP VS Local Rice, And Dynamic Marketing Capabilities on Marketing Performance : a Case Study on the West Kalimantan Provincial Government’s Cheap Food Movement - Hendra, Hendra; Venebis, Venebis; Nurcholis, Lutfi (Syntax Corporation, 2025)
This mixed-method study investigates consumer choice between nationally subsidized rice (SPHP) and local rice in the West Kalimantan Cheap Food Movement (GPM) program. This study examines positional advantage and dynamic marketing ability. Quantitative findings indicate the price and availability advantages of SPHP rice. Qualitative data reveal consumer perceptions of the quality of local rice. This study concludes with implications for food security programs.